Implementation and Training of a VBA for Service Information System using Waterfall Model: A Case Study of Laundry Hasanah - Zulfahmi Noor; Lintang Puja Prameswarie; Siti Irma Fadilla; Sheila Carol Dorothy Kemur; Arif Mustakim; Nur Ainun Musvirah; Nurmasitya Kemalaintan; Fauziah Fauziah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The advancement of information technology has driven the digitalization of the MSME sector; however, most businesses still rely on manual systems that are inefficient and prone to errors. This issue is also encountered by Laundry Hasanah MSME in Berau Regency in managing its service operations. Therefore, this study aims to develop and implement a service information system based on Visual Basic for Applications (VBA) to improve data processing efficiency and enhance service quality, which is expected to have a significant impact on the business sustainability of Laundry Hasanah. The development and design method employed in this study and community service activity is the Waterfall model, consisting of the stages of analysis, design, implementation, and testing. The implementation results indicate that the system is capable of accelerating the recording process, reducing errors, and improving service quality in a more effective and accurate manner. Based on the design and implementation of the VBA based laundry service information system, it can be concluded that the application was systematically designed and developed in accordance with the Waterfall model. Each stage, from requirements analysis to maintenance, was carried out sequentially and consistently, ensuring that the development process was structured, controlled, and capable of minimizing potential errors.